The naive moral as a possible mental attitude behind the outlaw-motif in English medieval narratives and its influence upon the structure of Thomas Lodge's "Rosalynde" and Shakespeare's "As you like it" - Ruthrof, Horst (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1967)
The idea for this thesis originated in a seminar concerned with short forms of epic literature. It is meant to throw some light on the development of rudimentary narrative technique, especially on the influence a particular motif can exert on a writer's mind and the final form of his work. Preface, p. 7.
Keywords: Literature and morals; English literature -- Middle English, 1100-1500; English literature -- Early modern, 1500-1700